The theory of reflexivity: A non-stochastic randomness theory for business schools only? - Dirk Ehnts; Miguel Carrión Álvarez (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2013)
The Alchemy of Finance, a book written by George Soros (1987) on the workings of financial markets, 'has found a place in the reading lists of business schools as distinct from economics departments', according to the author (2003, 4). His theory of reflexivity, which is at the center of the book, states that interdependence exists between the cognitive and manipulative functions of market participants. While Soros claims that imperfect knowledge rules on financial markets, academic orthodoxy assumes perfect knowledge and hence displays - in the absence of external shocks - financial markets as efficient. We review the work of Soros on reflexivity and follow up his claim that it can be used to attack the efficient market hypothesis. Both are discussed and then the ideas of Soros are compared to those of Post-Keynesian economics. We argue that Soros' book is mainly ignored by neo-classical economists because they disagree with his axioms, and by heterodox economists because his ideas are not new.
Keywords: B26; D8; 330; efficient market hypothesis; theory of reflexivity; George Soros